2014
DOI: 10.1210/en.2014-1083
|View full text |Cite
|
Sign up to set email alerts
|

FGF-21 and Skeletal Remodeling During and After Lactation in C57BL/6J Mice

Abstract: Lactation is associated with significant alterations in both body composition and bone mass. Systemic and local skeletal factors such as receptor activator of nuclear factor κ-B ligand (RANKL), PTHrP, calcitonin, and estrogen are known to regulate bone remodeling during and after lactation. Fibroblast growth factor 21 (FGF-21) may function as an endocrine factor to regulate body composition changes during lactation by inducing gluconeogenesis and fatty acid oxidation. In this study, we hypothesized that the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
55
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 35 publications
6
55
1
Order By: Relevance
“…Another recent study found that FGF21 circulates at high levels in lactating mice (101). This is a counterregulatory factor that stimulates gluconeogenesis and fatty acid oxidation during substrate deficiency, and a member of a subfamily that includes FGF23 (724).…”
Section: Animal Datamentioning
confidence: 99%
See 3 more Smart Citations
“…Another recent study found that FGF21 circulates at high levels in lactating mice (101). This is a counterregulatory factor that stimulates gluconeogenesis and fatty acid oxidation during substrate deficiency, and a member of a subfamily that includes FGF23 (724).…”
Section: Animal Datamentioning
confidence: 99%
“…Bone turnover markers are increased during lactation, with bone resorption markers generally showing proportionately greater increases than in bone formation markers (35,101,330,477,478,580,956,994). These alterations in bone turnover markers can be prevented by treatment with a bisphosphonate, OPG, and high-dose estradiol treatment (37, 956).…”
Section: Animal Datamentioning
confidence: 99%
See 2 more Smart Citations
“…In states in which SNS tone is high (eg, cold exposure, FGF-21 excess), beige cells are found in the subcutaneous or inguinal depot. (42) On the other hand, bone mass is significantly reduced during high SNS tone, principally due to activation of the b2 receptor on osteoblasts. Activation of this receptor suppresses the key transcription factor, ATF4, while it enhances RANKL production.…”
mentioning
confidence: 99%